Distinct sets of olfactory receptors highly expressed in different human tissues evaluated by meta-transcriptome analysis: Association of OR10A6 in skin with keratinization - Nakanishi, Shinobu; Tsutsui, Taiki; Itai, Nao; Denda, Mitsuhiro (Frontiers in Cell and Developmental Biology, 2023)
Olfactory receptors (ORs) are expressed in many tissues and have multiple functions. However, most studies have focused on individual ORs. Here, we aimed to conduct a comprehensive meta-transcriptome analysis of OR gene expression in human tissues by using open-source tools to search a large, publicly available genotype-tissue expression (GTEx) data set. Analysis of RNA-seq data from GTEx revealed that OR expression patterns were tissue-dependent, and we identified distinct sets of ORs that were highly expressed in 12 tissues, involving 97 ORs in total. Among them, OR5P2, OR5P3 and OR10A6 were associated with skin. We further examined the roles of these ORs in skin by performing weighted gene correlation network analysis (WGCNA) and c3net analysis. WGCNA suggested that the three ORs are involved in epidermal differentiation and water-impermeable barrier homeostasis, and OR10A6 showed the largest gene sub-network in the c3net network. Immunocytochemical examination of human skin keratinocytes revealed a sparse expression pattern of OR10A6, suggesting that it is not uniformly distributed among all keratinocytes. An OR10A6 agonist, 3-phenylpropyl propionate (3PPP), transiently increased intracellular Ca2+ concentration and increased cornified envelope (CE) production in cultured keratinocytes. Knock-down of OR10A6 diminished the effect of 3PPP. Overall, integration of meta-transcriptome analysis and functional analysis uncovered distinct expression patterns of ORs in various human tissues, providing basic data for future studies of the biological functions of highly expressed ORs in individual tissues. Our results further suggest that expression of OR10A6 in skin is related to epidermal differentiation, and OR10A6 may be a potential target for modulation of keratinization.